The Effect of Stunting Reduction Acceleration Policy Implementation on Posyandu Service Utilization - Multy Syaddam Nirwan; Fadly Umar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Stunting remains a major chronic nutritional problem in Indonesia. Sigi Regency, Central Sulawesi, experienced a significant increase in stunting cases in 2024 despite the implementation of Presidential Regulation Number 72 of 2021 on the Acceleration of Stunting Reduction, including mentoring by the Family Assistance Team (TPK). As Posyandu serve as the frontline for stunting detection and prevention, their utilization by mothers of children under five is an important indicator of policy success at the community level. This study aimed to analyze the effect of stunting reduction acceleration policy implementation on Posyandu service utilization among mothers of children under five in Palolo Subdistrict, Sigi Regency. Methods: This cross-sectional study involved all mothers with children aged 0–59 months in Palolo Subdistrict, Sigi Regency. The sample size, calculated using the Slovin formula (10% margin of error), was 100 respondents, selected through proportionate stratified random sampling by village. Data were collected using a validated structured questionnaire and analyzed using univariate, bivariate (Chi-Square), and multivariate (multiple logistic regression) analyses. Results: Of the 100 respondents, 62.0% were classified as routine users of Posyandu services. Good maternal knowledge (62.0%), intensive TPK/KPM mentoring (52.0%), and exposure to policy dissemination (53.0%) were each significantly associated with Posyandu utilization in the bivariate analysis (p<0.05). Multivariate analysis showed that TPK/KPM mentoring had the largest effect (Adjusted OR=5.71; 95% CI: 2.07–15.78; p=0.001), followed by maternal knowledge (Adjusted OR=3.61; p=0.011), exposure to policy dissemination (Adjusted OR=3.18; p=0.018), and family support as a covariate (Adjusted OR=2.63; p=0.041), with the model explaining 48.2% of the variance in Posyandu utilization (Nagelkerke R²=0.482; classification accuracy 78.0%). Conclusion: The implementation of the stunting reduction acceleration policy significantly affected Posyandu service utilization among mothers of children under five in Palolo Subdistrict, with TPK/KPM mentoring emerging as the most influential factor. These findings indicate that the rise in stunting cases in Sigi Regency in 2024 was associated with variation in the effectiveness of policy implementation at the field level. Strengthening TPK/KPM mentoring capacity, providing continuous education, and expanding policy dissemination are essential to improve Posyandu utilization and support the acceleration of stunting reduction.